Prevalence, extent and severity of severe periodontal destruction in an urban Aboriginal and Torres Strait Islander population. (6th February 2014) - Roberts‐Thomson, KF; Do, LG; Bartold, PM; Daniels, J; Grosse, A; Meihubers, S
Abstract Background The aim of this study was to document the three main indicators of severe periodontal destruction and to evaluate factors associated with those indicators in an urban Indigenous population in Australia. Methods A cross‐sectional survey of a convenience sample of Aboriginal adults from an Australian urban area was undertaken. Socio‐demographic data and smoking status were collected by interview and health status by a medical record audit. Clinical attachment loss (CAL) was used to determine prevalence, extent and severity of severe periodontitis. Factors with significant association with periodontal indicators at bivariate level were further included in multivariable analysis controlling for age and gender. Results A total of 251 Aboriginal adults participated in the study. The proportion with severe periodontitis was 11.9% (95% CI: 7.6–16.3), extent: 5.0% (95% CI: 3.3–6.7) and severity: 5.3 mm (95% CI: 5.0–5.6). These estimates are significantly higher than that of other Australians. Current smokers had significantly higher prevalence rate (PR) of severe periodontitis: PR = 2.8 (95% CI: 1.3–6.0). People with diabetes and current smokers had significantly higher extent of sites with CAL 6+ mm: 1.9 (1.1–3.3) and 2.1 (1.2–3.6) respectively. Having diabetes was associated with significantly higher severity score (β: 0.96 (SE: 0.47)). Conclusions A high proportion of this urban Aboriginal population had severe periodontal disease related to smoking and diabetes.